Urban sustainable development: the cost of pursuing SDGs - Franco, Stefano (TeMA - Journal of Land Use, Mobility and Environment, 2022)
<span class="NormalTextRun SCXW186497617 BCX0" data-ccp-parastyle="Abstract" data-ccp-parastyle-defn=""ObjectId":"00000000-0000-0000-0000-000000000000|0","ClassId":1073872969,"Properties":[469775450,"Abstract",201340122,"2",134234082,"true",134233614,"true",469778129,"Abstract",335572020,"1",469777841,"Tahoma",469777842,"Tahoma",469777844,"Tahoma",469769226,"Tahoma",268442635,"18",335551547,"1033",335559740,"276",201341983,"0",335559739,"0",335551550,"6",335551620,"6",469778324,"Normal"]">Starting from the relationship between urban planning and mobility management, TeMA has gradually expanded the view of the covered topics, always following a rigorous scientific in-depth analysis. This section of the Journal, Review Notes, is the expression of a continuous updating of emerging topics concerning relationships among urban planning, mobility and environment, through a collection of short scientific papers. The Review Notes are made of four parts. Each section examines a specific aspect of the broader information storage within the main interests of TeMA Journal. In particular, the Economy, business and land use section aims at presenting recent advancements on relevant topics that underlie socio-economic relationships between firms and territories. The present note aims at highlighting the costs associated to the UN Sustainable Development Goals. The hight investment costs and the gap that still divides cities from the achievement of the sustainable targets shed lights on the need to incentivize both public and private investments.